2016
DOI: 10.1016/j.earscirev.2016.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Using multi-tracer inference to move beyond single-catchment ecohydrology

Abstract: International audienceProtecting or restoring aquatic ecosystems in the face of growing anthropogenic pressures requires an understanding of hydrological and biogeochemical functioning across multiple spatial and temporal scales. Recent technological and methodological advances have vastly increased the number and diversity of hydrological, bio-geochemical, and ecological tracers available, providing potentially powerful tools to improve understanding of fundamental problems in ecohydrology, notably: 1. Identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
162
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 149 publications
(170 citation statements)
references
References 377 publications
4
162
0
Order By: Relevance
“…The work of Ocampo et al (15) suggested interpreting NO3 transport and transformation within a riparian zone using a Damköhler number, which is the ratio of a characteristic residence time, with importance (28) that has been documented by several empirical (5,16,17) and numerical (29,30) investigations, to the characteristic time of the pertinent biogeochemical reaction. Recent investigations also proposed this approach to interpret hyporheic processes (31,32), and they adapted it to quantify the hyporheic biogeochemical response at both bedform (33) and reach (34) scales. Here, we capitalized on these advances to depict the observed scaling effect on N 2 O emissions across riverine networks (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The work of Ocampo et al (15) suggested interpreting NO3 transport and transformation within a riparian zone using a Damköhler number, which is the ratio of a characteristic residence time, with importance (28) that has been documented by several empirical (5,16,17) and numerical (29,30) investigations, to the characteristic time of the pertinent biogeochemical reaction. Recent investigations also proposed this approach to interpret hyporheic processes (31,32), and they adapted it to quantify the hyporheic biogeochemical response at both bedform (33) and reach (34) scales. Here, we capitalized on these advances to depict the observed scaling effect on N 2 O emissions across riverine networks (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Spatial and temporal scales for use of different hydrological tracers (Abbott et al, ; Aggarwal, ; Newman et al, ). The black box represents groundwater age tracers applicable on scales from small catchments to large basins that span different temporal scales.…”
Section: Quantifying Water Ages In the Critical Zonementioning
confidence: 99%
“…While this large labile DOC addition in Experiment 4 demonstrated that an increased supply of acetate promotes increased NO 3 − removal, it did not have a strong effect on overall denitrification rates, suggesting that denitrification in this lake SWI is not primarily controlled by N or C reaction substrate limitations. Thus, it is likely limited by exposure timescales of the solutes in the SWI, which are controlled by the prevailing transport conditions, similar to those seen in other freshwater SWIs (Abbott et al, ; Briggs et al, ; Marzadri et al, ; Zarnetske et al, ). In this experiment, the median residence time through the SWI was only 0.97 hr, which was slightly less than previous experiments when lake levels were higher (Table ).…”
Section: Resultsmentioning
confidence: 93%